Russian-Ukrainian War of 2014–2017 as a consequence of the incompleteness of the national liberation Ukrainian revolution of 1917–1921 - Sytnyk, O. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract Introduction. The Ukrainian revolution of 1917–1921, which had a pronounced nationalist character, because of a number of objective and subjective circumstances were incomplete. Thus, this not only led to the Bolshevik occupation of a significant part of Ukraine, but also became the main reason for the continuation of the national liberation struggle of Ukrainians in our time. Purpose. The purpose of this article is to characterise the modern Russian-Ukrainian war 2014–2017 as a consequence of the incompleteness of the Ukrainian national liberation revolution. Results. Permanent looking for revolutionary transformation in Russia, the belief that national problems can be solved within the framework of the Russian revolutionary democratic front resulted in the omission of the chance which gave the Ukrainians the ability to create their own independent state. This not only led to the defeat of the national-liberation competitions of 1917–1921 years, but also contributed to further the total destruction of Ukrainians throughout the existence of the Bolshevik government. And naturally, modern warfare was a continuation of the centuries-long expansion of the Muscovite state, with its Imperial creatures: autocracy and Bolshevism and Putinism with neocons against Ukraine. At the beginning of the XXI century we are faced with the resuscitation of the neo-Bolshevism of the authoritarian tendencies in contemporary Russia, mainly Putin’s regime. Originality. In the modern Russian-Ukrainian war Ukrainian national revolution gets a new, decisive content. It is only with a successful for Ukraine, the completion of this war will be possible to obtain a true, real independence of our state. Conclusion. Our historical experience shows that the restructuring of Ukrainian state-building strategies need to change and rebuild its basic principles, namely: - in the formation of social ideology is strongly to get rid of pacifist Filosofem; - the nation should be educated on the principles of national heroism, the priority of state and national interests; - it is necessary to abandon the illusion of a vision of international relations and firmly apply the logic of geopolitics, according to which Ukraine as a state located in the geostrategic area, cannot afford to relax militarily and deceptive conduct international peace policy, not to respond to the threat posed by neighboring Imperial powers, especially Russia; - Russian imperialism has chauvinistic content, and therefore it is particularly aggressive against Nations which in some measure raises the "leading role", the "mission" of the Russian nation and state; it is clear that in this case the Ukrainian nation and the state are under a major blow to Russian expansionism and chauvinism, because they carry the main challenges of the Russian Imperial identity: they "select" the Russians have a historical heritage and culture of the past (until XVIII century), breaking a large number of Russian velikoderzhavnitska myths as "fraternal peoples", and "civilizational role" of the Russian Empire "justifiability" of Russian communism, and so etc., deprive the Empire of geopolitical scale, because cutting her off from the strategic space of the black sea, so Ukraine’s foreign policy should be as watchful against Russian imperialism and rationally deliberate about its threats; - the current Russian-Ukrainian war is not only reaffirms our historical insights, but also stimulates more radical changes in the sphere of national self-education and internal Ukrainian politics, namely, to broader and deeper use in them of philosophical principles and ideas of strong-willed Ukrainian nationalism.